Clathrin- and caveolae- independent endocytosis of newcastle disease virus strain AF2240 into hela cancer cell line - Sukram, Nurhazwani (2014)
Newcastle disease virus (NDV), a Paramyxoviridae, is an enveloped virus with a single stranded, non-segmented negative sense RNA genome. Studies on oncolytic activity of certain strain of NDV have yielded encouraging results and increased the interest of researcher to develop it as cancer therapy. Despite the interest, the exact mechanism of how the virus induces oncolysis is not known and the process of its entry into cells is also not fully understood. To understand the entry process, the present study was designed with the main objective to determine the endocytic pathway, mainly receptor mediated, of a velogenic local strain of NDV strain AF2240 into HeLa cancer cells. The objectives were divided into three parts, which are, to evaluate the cytotoxicity effects of chlorpromazine (CPZ) and genistein on HeLa cell viability; to determine the effect of chlorpromazine (CPZ) and genistein on NDV nucleocapsid protein (NP) expression; and to study the involvement of caveolin-1 protein in NDV AF2240 entry into HeLa cells. It was hypothesized that the NDV enter the cells via caveolae-mediated endocytosis, and caveolin-1 protein will be involved in the process. Data from the study showed that the IC50 of CPZ is 5.829 (± 0.075) μM and as for genistein, the IC50 is above 500 μM. It was found that in dose- and time- dependent manner, CPZ does not cause any effect to the NDV NP expression, whereas genistein inhibits the NP expression at the concentration of 250 μM and at 3 h p.i with the same concentration. However, the data obtained from confocal analysis showed that the internalization of NDV into HeLa cells might not be mediated by caveosomes (a caveolincoated endocytic vesicle) since there is not caveolin-1 found when NDV internalized into the cells. This data suggested NDV AF2240 might deploy an alternative method of entry, which is clathrin-independent, cholesterol-dependent endocytosis that is not dependent on the presence of caveolin-1. Information regarding these steps in viral entry would shed light into understanding the virus mechanism towards cancer cell killing mechanism. These might help in the rational design for NDV oncolytic studies.